Post-tetanic potentiation in the rat calyx of Held synapse - Habets, Ron LP (Blackwell Science Inc, 2005)
We studied synaptic plasticity in the calyx of Held synapse, an axosomatic synapse in the auditory brainstem, by making whole-cell patch clamp recordings of the principal cells innervated by the calyces in a slice preparation of 7- to 10-day-old rats. A 5 min 20 Hz stimulus train increased the amplitude of excitatory postsynaptic currents (EPSCs) on average more than twofold. The amplitude of the synaptic currents took several minutes to return to control values. The post-tetanic potentiation (PTP) was accompanied by a clear increase in the frequency, but not the amplitude, of spontaneous EPSCs, which returned to baseline more rapidly than the potentiation of evoked release. The size of the readily releasable pool of vesicles was increased by about 30%. In experiments in which presynaptic measurements of the intracellular calcium concentration were combined with postsynaptic voltage clamp recordings, PTP was accompanied by an increase in the presynaptic calcium concentration to about 210 nm. The decay of the PTP matched the decay of this increase. When the decay of the calcium transient was shortened by dialysing the terminal with EGTA, the PTP decay sped up in parallel. Our experiments suggest that PTP at the calyx of Held synapse is due to a long-lasting increase in the presynaptic calcium concentration following a tetanus, which results in an increase in the release probability of the vesicles of the readily releasable pool. Although part of the PTP can be explained by a direct activation of the calcium sensor for phasic release, other mechanisms are likely to contribute as well.